The Functional Network of PrkC and Its Interaction Proteins in Bacillus subtilis Spores - Kangyi Mu; Tianlin Cui; Zequn Zhang; Yicong Shi; Chen Fang; Li Dong; Xiaosong Hu (Microorganisms)
In the food industry, food spoilage caused by spores is a pressing scientific challenge that needs to be addressed urgently, and spore germination is a key approach to solving this problem. Studies have shown that peptidoglycan-induced spore germination represents a novel mechanism of action, which can bind to the PASTA domain of the serine/threonine kinase PrkC. However, the signaling mechanism of peptidoglycan-induced spore germination remains unclear. This study focuses on Bacillus subtilis, using pull-down experiments to screen for proteins interacting with PrkC. There are 80 interaction proteins of PrkC that were identified in the spore. GO analysis reveals that PrkC-interacting proteins in the spore are mainly involved in metabolic processes, cell part and catalysis. KEGG results indicate that PrkC-interacting proteins in the spore are mainly involved in RNA degradation, quorum sensing, oxidative phosphorylation, etc. Additionally, proteins are categorized into six groups by function based on events that may be associated with post-germination triggered by peptidoglycan-induced activation of the PrkC signaling pathway, including “stimulate translation initiation” and “ATP synthesis and energy metabolism”. The experimental results provide a theoretical basis for further elucidating the signaling mechanism of PrkC, revealing the signaling pathway of peptidoglycan-induced spore germination, and identifying targeted inducers and repressors of spore germination.